2002
DOI: 10.2355/isijinternational.42.273
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ti on the Hot Ductility of Nb-bearing Steels in Simulated Continuous Casting Process.

Abstract: The hot ductility of as-cast Nb, Ti and Nb-Ti bearing low-carbon steels has been assessed. Hot tensile testing of in-situ melted specimens, replica examinations and thermodynamic modeling showed that addition of 0.014-0.04%Ti to 0.1%C-0.03%Nb-0.005%N steel leads to a large volume fraction of fine strain-induced precipitates at temperatures up to 1 000°C which seriously deteriorate the hot ductility, in spite of the type of prior thermal history. Generally, three types of precipitates, i.e. coarse boundary prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
3
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 15 publications
5
37
3
1
Order By: Relevance
“…Hot tensile testing of in situ melted samples, led to a large volume fraction of fine strain induced precipitates at temperatures as high as 1000 o C seriously impairing ductility as shown Fig.2.65 [150]. An increase in the Ti level led to even worse ductility.…”
Section: Titaniummentioning
confidence: 99%
See 2 more Smart Citations
“…Hot tensile testing of in situ melted samples, led to a large volume fraction of fine strain induced precipitates at temperatures as high as 1000 o C seriously impairing ductility as shown Fig.2.65 [150]. An increase in the Ti level led to even worse ductility.…”
Section: Titaniummentioning
confidence: 99%
“…Commercially, for low nitrogen steels (0.005%N), titanium levels are recommended to be 2~4 times the nitrogen level, although Turkdogan [68] has stated that the favoured ratio is 4. In contrast, when laboratory hot tensile tests are carried out, it is found that small additions of titanium lead to poor ductility [78,131,150], unless the cooling rate after casting is slow [79]. When simulated cooling rates are fast, as for thin slab casting, precipitation is always fine.…”
Section: Titaniummentioning
confidence: 99%
See 1 more Smart Citation
“…10, the formation of these particles may be likely that TiN parties precipitat firstly and then become the nucleation sites of precipitates containing Nb when the deformation occurs. 20) In addition, the formation of these particles may also be likely due to a combination of Nb(C, N) and Ti(C, N) which precipitate in the meantime in the process of deformation. 21) However, these particles are rarely found in lower temperature range.…”
Section: Thickness Of Ferrite Filmsmentioning
confidence: 99%
“…[12][13][14][15][16] A relatively large number of papers available in literature refers to as cast steels tested by cooling at various rates from the melting temperature or by reheating the cast structure from room temperature. 1,2,[6][7][8][9]12,13,[17][18][19][20] Under these conditions, the coarse grain structure and the segregation of alloying elements at boundaries strongly affects precipitation. On the contrary, less attention has been paid to hot ductility of wrought steels.…”
Section: Introductionmentioning
confidence: 99%